Many-Body Theory Calculations of Positron Scattering and Annihilation in H2, N2, and CH4 - Patterson, Charles (My University, 2023)
The recently developed ab initio many-body theory of positron molecule binding [J. Hofierka et al., Many-body theory of positron binding to polyatomic molecules, Nature (London) 606, 688 (2022)] is combined with the shifted pseudostates method [A. R. Swann and G. F. Gribakin, Model-potential calculations of positron binding, scattering, and annihilation for atoms and small molecules using a Gaussian basis, Phys. Rev. A 101, 022702 (2020)] to calculate positron scattering and annihilation rates on small molecules, namely H2, N2, and CH4. The important effects of positron-molecule correlations are delineated. The method provides uniformly good results for annihilation rates on all the targets, from the simplest (H2, for which only a sole previous calculation agrees with experiment), to larger targets, where high-quality calculations have not been available.
Keywords: C60/oligothiophene complexes; charge transfer (CT); Electroabsorption spectroscopy (EA)